2008
DOI: 10.1126/science.1157535
|View full text |Cite
|
Sign up to set email alerts
|

The Rag GTPases Bind Raptor and Mediate Amino Acid Signaling to mTORC1

Abstract: The multiprotein mTORC1 protein kinase complex is the central component of a pathway that promotes growth in response to insulin, energy levels, and amino acids, and is deregulated in common cancers. We find that the Rag proteins-a family of four related small guanosine triphosphatases (GTPases)-interact with mTORC1 in an amino acid sensitive manner and are necessary for the activation of the mTORC1 pathway by amino acids. A Rag mutant that is constitutively bound to GTP interacted strongly with mTORC1 and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

122
2,756
7
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,384 publications
(2,970 citation statements)
references
References 29 publications
122
2,756
7
10
Order By: Relevance
“…Therefore, under our experimental conditions, our results would support the idea that HMB acts mainly via the class I PI3K/Akt pathway,19 whereas it is described that L‐Leu exerts its action via the class III PI3K2, 31 that could mediate the activation of mTOR. In fact, it has been described that branched amino acids stimulate directly mTOR through a mechanism involving Rag GTPases 45. This alternate pathway has been described under amino acid deprivation,45 but during our experimental conditions without leucine starvation, there was no increase in protein synthesis nor in mTOR phosphorylation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, under our experimental conditions, our results would support the idea that HMB acts mainly via the class I PI3K/Akt pathway,19 whereas it is described that L‐Leu exerts its action via the class III PI3K2, 31 that could mediate the activation of mTOR. In fact, it has been described that branched amino acids stimulate directly mTOR through a mechanism involving Rag GTPases 45. This alternate pathway has been described under amino acid deprivation,45 but during our experimental conditions without leucine starvation, there was no increase in protein synthesis nor in mTOR phosphorylation.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, it has been described that branched amino acids stimulate directly mTOR through a mechanism involving Rag GTPases 45. This alternate pathway has been described under amino acid deprivation,45 but during our experimental conditions without leucine starvation, there was no increase in protein synthesis nor in mTOR phosphorylation. Up to this point, under non‐amino‐acid deprivation, our results indicated HMB as a more active inductor of protein synthesis.…”
Section: Discussionsupporting
confidence: 52%
“…Accordingly, expression of a constitutively active (GTP-bound) Gtr1 GTP , which interacted strongly with TORC1, rendered TORC1 partially resistant to leucine deprivation, while expression of a growth inhibitory GDP-bound Gtr1 GDP caused constitutively low TORC1 activity. In line with this proposed model in yeast, two complementary studies in Drosophila and mammalian cells have also reported that the conserved Rag GTPases act as upstream regulators of TORC1 and play important roles in coupling amino acid-derived signals to TORC1 (Kim et al 2008;Sancak et al 2008).…”
Section: How Is Tor Signalling Regulated?mentioning
confidence: 60%
“…Amino acid levels are linked to mTOR through a mechanism that is dependent, at least to some extent, on p62/ SQSTM1 (Duran et al 2011): mTORC1 associates with the amino acid sensing Rag family of small GTPases (Kim et al 2008;Sancak et al 2008) on the surface of lysosomes (Sancak et al 2010). p62/SQSTM1 mediates this process by associating with Raptor, a subunit of the mTORC1 complex, and the Rag GTPases, thereby forming a high molecular weight complex that relays the signal from amino acids to the mTORC1 pathway (Duran et al 2011).…”
Section: Amino Acid Sensing: Mtormentioning
confidence: 99%